Armadillo coactivates transcription driven by the product of the Drosophila segment polarity gene dTCF. - van de Wetering, M.; Cavallo, R.; Dooijes, D.; van Beest, M.; van Es, J.; Loureiro, J.; Ypma, A.; Hursh, D.; Jones, T.; Bejsovec, A.; Peifer, M.; Mortin, M.; et al. (Cell, 1997)
The vertebrate transcription factors TCF (T cell factor) and LEF (lymphocyte enhancer binding factor) interact with beta-catenin and are hypothesized to mediate Wingless/Wnt signaling. We have cloned a maternally expressed Drosophila TCF family member, dTCF. dTCF binds a canonical TCF DNA motif and interacts with the beta-catenin homolog Armadillo. Previous studies have identified two regions in Armadillo required for Wingless signaling. One of these interacts with dTCF, while the other constitutes a transactivation domain. Mutations in dTCF and expression of a dominant-negative dTCF transgene cause a segment polarity phenotype and affect expression of the Wingless target genes engrailed and Ultrabithorax. Epistasis analysis positions dTCF downstream of armadillo. The Armadillo-dTCF complex mediates Wingless signaling as a bipartite transcription factor.